Featured Article: Trajectories of Glycemic Control Over Adolescence and Emerging Adulthood: An 11-Year Longitudinal Study of Youth With Type 1 Diabetes. (16th May 2017) - Helgeson, Vicki S; Vaughn, Abigail Kunz; Seltman, Howard; Orchard, Trevor; Libman, Ingrid; Becker, Dorothy
Abstract: Objective: To identify trajectories of glycemic control over adolescence and emerging adulthood and to test whether demographic and psychosocial variables distinguished these trajectories. Methods: We enrolled 132 youth with type 1 diabetes when they were average age 12 and followed them for 11 years. We used group-based trajectory modeling to identify distinct patterns of glycemic control, and examined whether age 12 demographic and psychosocial variables distinguished the subsequent trajectories. Results: We identified 5 trajectories of glycemic control: stable on target, stable above target, volatile late peak, stable high, and inverted U. Parent social status and household structure distinguished the more problematic trajectories from the stable on target group. Friend conflict, psychological distress, unmitigated communion, and self-care behavior at age 12 distinguished problematic glycemic control trajectories from the stable on target group. Conclusions: These results can be used to identify youth who are at risk for deteriorating glycemic control over adolescence.